Pengaruh Permainan Loose Parts terhadap Kreativitas Anak Usia Dini di Ra Al-Ma’arif - Amelia Gani; Mita Sari; Arischa Putri Dama; Ajeng Molamahu; Dzihan Miolo; Sri Nadya Sahrain (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This research was motivated by the low level of creativity among early childhood children at RA Al-Ma’arif, Gorontalo City, as indicated by children’s limited ability to express ideas, create varied forms, and develop imaginative works independently. This study aimed to determine the effect of loose parts play on early childhood creativity. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The sample consisted of 12 children, divided into an experimental group of 6 children and a control group of 6 children. Data were collected through observation, tests, and documentation using a validated creativity assessment instrument. Data analysis was conducted using descriptive statistics and non-parametric inferential analysis with the Wilcoxon test. The results showed that children’s creativity in the experimental group increased after participating in loose parts play activities, as indicated by a higher posttest mean score compared to the pretest score. Statistical testing also demonstrated a significant effect of loose parts play on children’s creativity. Children became more capable of generating ideas, combining materials, and producing varied and original creations. It can be concluded that loose parts play is effective in improving early childhood creativity and can be used as an innovative and meaningful learning medium in early childhood education.